The Economic and Strategic Impact of China’s Rising Influence in Africa: A case Study in Nigeria and Zambia - Tanyi-Tang, George (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The rapidly increasing level of engagement between China and African states have attracted considerable scholarly attention and debates. Two distinct camps have formed around these debates, namely: “Sino-Optimism” and “Sino-Pessimism”. For Sino-optimists, China’s interest in Africa is potentially good for the continent and holds the potential of transforming Africa economically and technologically. For Sino Pessimists on the other hand, the opposite is the case as they believe that the relationship is dangerous for the international system. This point is often exemplified by pointing out China’s willingness to protect autocratic leaders in Africa by providing loans without incentives such as democratization and respect for human rights. At the heart of the debates between these schools of thought have been two fundamental issues. Firstly, scholars have considered the extent to which China’s influence have impacted African economies directly. Secondly, some have asserted that the nature of the relationship potentially exposes African states to a neo imperialistic dependency on China which essentially gives China economic and political dominion over the states. By Examining Nigeria and Zambia, two uniquely different states which have significantly different relationships with China, this thesis explores these two fundamental issues, exploring the history and strategic importance of the Sino-African relationship, as well as examining the relevant economic data. The research finds conclusive evidence of China’s positive effect on African economies via foreign Direct Investments (FDI) as well as infrastructure development projects. It also concludes that a neo-imperialistic dependency begins to emerge between some African States such as Zambia and the People’s Republic of China, this is evidenced by a governmental dependence on Chinese foreign aid as well as piling national debts owed by African states to China. Keywords: Sino-Optimism, Sino-Pessimism, Democratization, Neo-imperialism, Foreign Aid, National Debt, Foreign Direct Investment

ÖZ:Çin ve Afrika devletleri arasında hızla artan etkileşim düzeyi, önemli bilimsel ilgi ve tartışmalara neden oldu. Bu tartışmalar etrafında iki ayrı kamp oluştu: "Çin İyimserlik" ve "Çin-Kötümserlik". Çin iyimserleri için Çin’in Afrika’ya ilgisi kıta için potansiyel olarak iyidir ve Afrika’yı ekonomik ve teknolojik olarak dönüştürme potansiyeline sahiptir. Çin-Kötümserler için ise, ilişkinin uluslararası sistem için tehlikeli olduğuna inandıkları için durum tam tersidir. Bu nokta, Çin’in Afrika’daki otokratik liderleri, demokratikleşme ve insan haklarına saygı gibi teşvikler olmadan krediler vererek korumaya istekli olduğunun gösterilmesiyle örneklendirilir. Bu düşünce okulları arasındaki tartışmaların merkezinde iki temel mesele vardır. İlk olarak, bilim adamları Çin'in etkisinin Afrika ekonomilerini ne ölçüde doğrudan etkilediğini değerlendirdiler. İkinci olarak, bazıları, ilişkinin doğasının potansiyel olarak Afrika devletlerini Çin'e neo-emperyalist bir bağımlılığa maruz bıraktığını ve bunun da Çin'e esasen devletler üzerinde ekonomik ve politik hakimiyet verdiğini iddia etti. Bu tez, Çin ile önemli ölçüde farklı ilişkileri olan benzersiz iki farklı devlet olan Nijerya ve Zambiya'yı inceleyerek, bu iki temel konuyu araştırıyor, Çin-Afrika ilişkisinin tarihini ve stratejik önemini araştırıyor ve ilgili ekonomik verileri inceliyor. Araştırma, altyapı geliştirme projelerinin yanı sıra yabancı Doğrudan Yatırımlar (DYY) yoluyla Çin’in Afrika ekonomileri üzerindeki olumlu etkisine dair kesin kanıtlar buluyor. Ayrıca, Zambiya ve Çin Halk Cumhuriyeti gibi bazı Afrika Devletleri arasında neo-emperyalist bir bağımlılığın ortaya çıkmaya başladığı sonucuna varıyor; bu, hükümetin Çin dış yardımına bağımlılığının yanı sıra Afrika devletlerinin Çin'e borçlu olduğu usual borçların birikmesiyle kanıtlanıyor. Anahtar Kelimeler: Çin-İyimserlik, Çin-Kötümserlik, Demokratikleşme, Yeni emperyalizm, Dış Yardım, Ulusal Borç, Doğrudan Yabancı Yatırım.
Master of Arts in International Relations. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2021. Supervisor: Asst. Prof. Dr. Nuray Ibryamova.
Keywords: China-Foreign Relations-Economic Relations-Nigeria; Oil fields-Political aspects-Nigeria; Petroleum industry and trade-Nigeria; Oil fields-Economic aspects-Nigeria--China; Politics and government-Nigeria; Sino-Optimism; Sino-Pessimism; Democratization; Neo-imperialism; Foreign Aid; National Debt; Foreign Direct Investment